METODE TWO STAGE LEAST SQUARE (Studi Kasus di Kabupaten Banyuwangi) - Feby Indriana Yusuf (TRANSFORMASI, 2023)
The Two-Stage Least Squares (2SLS) method is used to ascertain the relationship between simultaneous equations, where each dependent variable in the model has a simultaneous relationship. This study explains the process that can be undertaken to estimate simultaneous equation models using the 2SLS method. The case study selected is about the relationship between residential area variables and employment variables. Based on the analysis results, the final conclusion is that the 2SLS steps have been executed, and there is a significant relationship between the residential area and the employment of the population in BanyuwangiRegency.